Introduction - Panieri, Giuliana; Stiller-Reeve, Mathew; Peftieva, Olena (Septentrio Educational, 2023)
This book consists of fifteen interdisciplinary lesson plans that inspire us to learn more about the ocean and our sense of it. Kindergarten and high school teachers are our primary audience, but they are not the only ones. We hope people of all ages can use them. Parents can experiment with their children at home. Some classes can be tried at retirement homes or local youth groups. Older students can use other plans as a guide for teaching younger students or at science fairs. All lesson plans were developed within the framework of the research project entitled "Expanding knowledge about methane in the Arctic" (AKMA project number 287869). The AKMA project was funded by Science Norway and led by UiT The Arctic University of Norway in collaboration with the US Woods Hole Oceanographic Institution (Woods Hole).